Analysis of Ambon City Community Interest in Investment in Government Securities (SBN) Perspective of Theory of Planned Behaviour - Laisila, Maya; Purimahua, Sarlotha Yuliana (Manunggal Halim Jaya, 2024)
The increasing number of capital market investors is a potential government funding source. However, the single investor identification (SID) data from PT Custodian Sentral Efek Indonesia (KSEI) shows that the number of Ambon City investors is only 0.03% nationally, especially investors in Government Securities instruments (SBN). In response to the gap that occurred, this research was conducted to analyze Ambon City's investment interest in government securities and examine the psychological and social factors underlying Ambon City's interest in investing in government securities. The research method is descriptive qualitative, with informants selected by purposive sampling using specific criteria. Primary data sources came from informants and secondary through documents, books, and journals. Data collection techniques through interviews, observation, and documentation were then analyzed using the theory of Planned Behaviour and source triangulation techniques to ensure data validity. The results showed that (1) the interest of the Ambon City community in investing in government securities increased but was still low, (2) the low investment demand was influenced by the level of financial literacy of the community, the perception / consumptive culture of the community and the supporting/inhibiting factors that arose in the investment process.